Pulau Osi: A Collaborative Strategy for Community-Based Mangrove Ecotourism Management - Kaliky, Fitriyanti; Djumat, Juni La; Umar, Dewi Bin; Sangadji, Suman; Simataw, Gusmianti; Latuamury, Bokiraiya (Jurnal Agrohut, 2025)
Pulau Osi is a coastal area with substantial potential for developing community-based mangrove ecotourism. This study aims to analyze the management and development strategies of the mangrove ecotourism area in Dusun Pulau Osi, West Seram Regency, using a qualitative descriptive approach and SWOT analysis. The findings indicate active community participation through the formation of groups such as Mangrove Lestari and Mina Mangrove Lestari. Internal strengths include abundant natural resources and scenic landscapes, while weaknesses lie in limited infrastructure and insufficient promotion. Externally, economic potential and technological advancement present key opportunities. The recommended strategy is an aggressive one, emphasizing the optimization of internal strengths and external opportunities through infrastructure development, digital promotion, and the creation of mangrove-derived products. The study concludes that the success of ecotourism management relies heavily on collaboration among communities, government, and private stakeholders in promoting conservation-based and locally-driven tourism development